ANALISIS PELAPORAN SEGMEN DAtAnfi PSAK NO.5 (EDlSt 1994) DAN PSAK NO. 5 (EDISI REVISI 2000) - Putriana Kristanti (Fakultas Bisnis UKDW, 2006)
The reseuch about accoanting standard, information content, the role : and the impact of segment information is develoveped, but ryot in Indonesia. The purpose of this research is to investigate about PSAK No. 5, the initialt and the revision. How far are the firm disclose their segment inforrntion afier ond before the standord is effective? The empirical evidence from 64 sample rtrus show that the standard, specially PSAK No, 5 (edisi wvisi 2A0Q is effeetive to motivde the firm discloseinformotion segwe#- PSAK Na, 5 (edisi revbi 20A is bapr thet PSAK No, 5 (edisi 1994). Utder PSAK No, 5 (ediii rzvisi 2AND &5.94% of the saruplef*nts redefmed their prinury segments. Tlere sre.4i.75% of the sample firms use line-of-business for the pi*wy segilent a.a@ition with geogrtc &e as tlre secodwy segment. Six items ae rcported in segment information of 4j.75oi sample Jirms. Segment revenue is reported by all of tle sample firms.Keywords : segnent information, PSAK No. 5 (lgg4),PSAK No. 5(Revisi 2ffi0); disclose, primary segtnent, secondary segment,line-of business, geografic area.